Une incursion en sociologie - Bok, Julien (Comptes Rendus. Physique)
Based on a remark by John von Neumann about the difficulty of managing N people, which suggests that it arises essentially from 2-to-2 interactions, we define a “difficulty” function of an organization. The optimization of this organization is obtained by minimizing this function. This leads to different hierarchical structures depending on the discipline maintained. We also present a study of the “power” of a hierarchical organization. Finally, we compare these results with sociological studies of existing companies. Some analogies to physical theories are highlighted.